Efforts to Improve Mathematics Learning Outcomes for Class III Place Value Materials at SDN Baros 04 with Value Pockets Teaching Aids - Dwi Erni Astutiningsih (Universitas Sebelas Maret, 2020)
This research was carried out with the aim of improving the mathematics learning outcomes of third grade students at SDN Baros 04 by using value pockets props on the number place value material. This type of research is classroom action research (CAR). The subjects were class III students, totaling 23 students. This CAR design includes planning, implementation, observation (evaluation), and reflection. Data collection techniques using observation, tests, and documentation. Data analysis used quantitative descriptive statistics. The results showed an increase in the percentage of student learning outcomes, this can be seen from each cycle. It was found that student learning outcomes increased compared to the pre-cycle average score of 53.91 to 57.82 in the first cycle, then to 71.30 in the second cycle. Thus, it can be concluded that the use of value bag teaching aids in the number place value material can improve student learning outcomes.